Astomonema southwardorum sp. nov., a gutless nematode dominant in a methane seep area in the North Sea - Austen, M. C.; Warwick, R. M.; Ryan, K. P. (Journal of the Marine Biological Association of the United Kingdom, 1993)
Locality: NA; Cabinet:
NeMys doc_id: 7449